Waqaf and Ibtida` in Al-Qur'an Recitation: A Study on Standard Indonesian and Madinah Mushafs in Surat al-Baqarah - Taufik, Ahmad Kamil (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to analyze the significance of waqaf and Ibtida` in the recitation of the Quran, specifically examining the differences in waqaf symbols between Mushaf Standar Indonesia and Mushaf Madinah in Surah al-Baqarah. The study also investigates the factors causing variations in waqaf symbols between these two Mushafs and explores the influence of these differences on the meaning and interpretation of the Quran. A qualitative research approach is employed, utilizing descriptive methods, literature review, and comparative analysis. The research focuses on Surah al-Baqarah in both Mushaf Standar Indonesia and Mushaf Madinah. Data analysis involves data reduction, presentation, verification, and concluding. The findings reveal the following: 1) Knowledge of waqaf and Ibtida is crucial in reading, translating, and interpreting the Quran; 2) There are similarities and differences in the positions of waqaf symbols between Mushaf Standar Indonesia and Mushaf Madinah in Surah al-Baqarah, classified into three types: First, both Mushafs place the waqaf symbol in the same location. Second, the Mushafs differ in placing waqaf symbols in the same location. Third, Mushaf Standar Indonesia symbolizes a waqaf symbol while Mushaf Madinah do not; 3) Factors causing differences in waqaf symbols between the two Mushafs include variations in understanding the arrangement of Quranic verses from the perspective of Balaghah sciences, encompassing 'Ilm al-Bayan, 'Ilm al-Ma'ani, and 'Ilm al-BÄdÄ«; 4) Overall, differences in Waqaf and Ibtida between the two Mushafs affect the possibilities of translation and interpretation of the Quran. In some cases, these differences and their impacts can be demonstrated. However, fundamentally, these variations reflect diversity rather than contradictory distinctions.